Pengembangan Modul Simulation Games tentang Kemampuan Berpikir Kreatif - Berlin Fanta Rosiani; Ariadi Nugraha (Kuras Institute, 2022)
This research is based on one of the preparations in welcoming the 21st century, students must have some ability in learning. The ability to think creatively is one of the skills that must be mastered in this century. This study aims to describe the development of the simulation games module on creative thinking and to describe the feasibility of the simulation games module to improve the thinking skills of the OSIS Management at SMP N 12 Yogyakarta from the assessment of material, media, and Guidance and Counseling service experts. This type of research is Research and Development with 4D models. Where the subjects in this study are material experts, media experts and counseling service experts. The result of this study is a simulation games module to improve creative thinking skills in the OSIS Management at SMP N 12 Yogyakarta. Where this research uses a 4D model, (Define, Design, Development, and Dissemination), but this research only reaches the Development stage and produces print media in the form of modules. As well as the results of the assessment of the simulation games module on the ability to think creatively in general, both in terms of media, materials, and services with details. The Simulation Games Module on Creative Thinking Ability is suitable for OSIS Management at SMP N 12 Yogyakarta.